#### Answer

$12 - 16i$

#### Work Step by Step

$(4 - 2i)^2 = 16 - 16i + 4i^2 = 16 - 16i + 4(-1) = 12 - 16i$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$12 - 16i$

$(4 - 2i)^2 = 16 - 16i + 4i^2 = 16 - 16i + 4(-1) = 12 - 16i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.